Kajian Kesesuaian Habitat Restocking Siput Gonggong (Laevistrombus sp.) di Teluk Kelabat Pulau Bangka - Supratman, Okto; Febrianti, Laras; Pratiwi, Fika Dewi; Farhaby, Arthur M; Okto Supratman (Journal of Tropical Marine Science, 2024)
The Dog conch is an important marine biota for ecology; besides that, it has economic value with high nutritional content. The purpose of this study was to analyze the density of the dog conch, to determine the appropriate environmental parameters for gonggong snails restocking, and to analyze the suitability of the location for the dog conchrestocking in Kelabat Bay, Bangka Island. This research was conducted from March to April 2021. The data collection of the dog conchand sea grasses used purposive sampling method. The highest density of the dog conchwas at station 7 with a density of 2000 (Ind/ha), while the lowest densities of the dog conchwere at stations 1, 4, 5 and 9 because dog conch was not founded. The results of the suitability of aquatic environmental parameters are categorized as still suitable for the life of gonggong snails. The suitability index values for the location of the the dog conch restocking at stations 6, 7, 8, 9 and 10 had values above 84-89 which is categorized as very suitable, while at stations 1, 2, 3, 4, 5 with values above 75-78 were categorized as appropriate. The results of the study indicate that the waters of Kelabat Bay have certain areas that are ideal to be used as a location for the dog conch restocking, so the recommended location for Dog Conch restocking is in the outer Kelabat Bay while still paying attention to sustainable fishing efforts.